2012
DOI: 10.1111/j.1439-0523.2012.01985.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of Co, a gene controlling columnar growth habit located on apple (Malus×domestica Borkh.) linkage group 10

Abstract: Tree architecture and shoot morphology are important factors in apple production systems. Because a columnar growth habit facilitates highdensity planting and labour-saving fruit production methods, columnar apple breeding programmes are spreading worldwide. Columnar growth habit is controlled by a single dominant gene, Co, on linkage group 10. Fine mapping of Co was conducted using 1000 F 1 progeny plants from 31 populations. Novel simple sequence-repeat (SSR) markers were developed based on the genome sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 23 publications
2
31
0
4
Order By: Relevance
“…They delimited the Co gene region to 196 kb, a similar size as in Bai et al (2012). However, the markers developed by Moriya et al (2012) Moriya et al (2012), but does not span the chromosomal location predicted for Co by Bai et al (2012). Furthermore, marker C18470-25831, which Bai et al (2012) found to be linked to Co, showed three recombinants in the mapping population of Baldi et al (2012).…”
Section: Phenotype Characteristics Of Columnar Type Apple Treesmentioning
confidence: 99%
See 1 more Smart Citation
“…They delimited the Co gene region to 196 kb, a similar size as in Bai et al (2012). However, the markers developed by Moriya et al (2012) Moriya et al (2012), but does not span the chromosomal location predicted for Co by Bai et al (2012). Furthermore, marker C18470-25831, which Bai et al (2012) found to be linked to Co, showed three recombinants in the mapping population of Baldi et al (2012).…”
Section: Phenotype Characteristics Of Columnar Type Apple Treesmentioning
confidence: 99%
“…The newly delimited region contains 20 annotated genes and 7 predicted genes, 3 of which code for homologs of Lateral Organ Boundaries Domain transcription factors in Arabidopsis (Majer and Hochholdinger 2011) and were thus considered the most likely candidates for Co (Bai et al 2012). Moriya et al (2012) also developed SSR markers based on the Golden Delicious genome sequence and used 1,000 F 1 individuals from 31 populations for linkage analysis. They delimited the Co gene region to 196 kb, a similar size as in Bai et al (2012).…”
Section: Phenotype Characteristics Of Columnar Type Apple Treesmentioning
confidence: 99%
“…DS4 adaptor was ligated to digest genomic DNA to perform genome walking [21,27]. Then attachment of DS5 adaptor was tried and successfully amplified apple S-RNase fragment [5]. Attachment of the DS5 adaptor to the forward primer slightly reduced PCR amplification of the target sequence, together with amplification of non-specific smear DNA band.…”
Section: Effective Use Of Ds6 Adaptor For Improvement Of a Dcaps Markermentioning
confidence: 99%
“…For example, the SSR (simple sequence repeat) -type DNA marker NZmsEB119405 for Cg locus estimates crown gall resistance of apple rootstock cultivars [4]. Another SSR-type DNA markers such as Mdo.chr10.14 for the Co locus is genetically linked to the columnar tree shape of apple scion cultivar 'Wijcik' [5]. We have also recently developed a sequencingbased DNA marker APPLid for determination of apple S alleles [6].…”
Section: Introductionmentioning
confidence: 99%
“…The application of MAS to apple-breeding programs has mainly focused on certain well-known traits of interest, including resistance to scab, flavor, firmness, columnar growth habit, and skin color (Takos et al, 2006;Bus et al, 2007;Zhu and Barritt, 2008;Moriya et al, 2012). For the skin color trait, it has been shown that a RAPD DNA marker derived from the red skin gene, Rf, is able to discriminate between most red and non-red apple cultivars, and has been used in advanced breeding selections (Cheng et al, 1996).…”
Section: Introductionmentioning
confidence: 99%